Trimodal Porous Hierarchical SSZ-13 Zeolite with Improved Catalytic Performance in the Methanol-to-Olefins Reaction - Zhu, Xiaochun; Hofmann, Jan P.; Mezari, Brahim; Kosinov, Nikolay; Wu, Leilei; Qian, Qingyun; Weckhuysen, Bert M.; Asahina, Shunsuke; Ruiz-Martinez, Javier; Hensen, Emiel J. M. (American Chemical Society, 2016)
Chabazite zeolites with trimodal porosity (native micropores of the CHA framework, an additional network of larger micropores of ∼0.5 nm, and mesopores) were synthesized by adding diquarternary ammonium-type surfactant C22–4–4 cations and fluoride anions in the synthesis of SSZ-13 zeolite. The hierarchical SSZ-13 zeolites are fully crystalline and exhibit similar acidity as bulk SSZ-13 zeolite. The increased diffusion rate in the hierarchical SSZ-13, proven by uptake experiments of bulky molecules and selective staining by thiophene oligomers, resulted in much slower catalyst deactivation in the methanol-to-olefins (MTO) reaction. Confocal fluorescent images of spent hierarchical SSZ-13 zeolites reveal homogeneous distribution of carbonaceous deposits, indicating that the micropore space has been completely utilized during the MTO reaction.
Keywords: zeolite; SSZ-13; porosity; deactivation; carbonaceous deposits; methanol-to-olefins; Taverne